2012
DOI: 10.1186/cc11316
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant micronutrients in the critically ill: a systematic review and meta-analysis

Abstract: IntroductionCritical illness is characterized by oxidative stress, which is a major promoter of systemic inflammation and organ failure due to excessive free radical production, depletion of antioxidant defenses, or both. We hypothesized that exogenous supplementation of trace elements and vitamins could restore antioxidant status, improving clinical outcomes.MethodsWe searched computerized databases, reference lists of pertinent articles and personal files from 1980 to 2011. We included randomized controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 69 publications
2
157
0
7
Order By: Relevance
“…The latest systematic review, including 21 trials, regarding antioxidant micronutrients in the critically ill confirm the mortality, length of stay and LICU findings by Visser et al, 100 and additionally report a significant reduction in duration of mechanical ventilation (WMD in days = -0.67, 95% CI -1.22 to -0.13, p-value = 0.02) with antioxidant supplementation. 110 Furthermore, antioxidants were associated with a significant reduction in overall mortality in patients with higher risk of death (> 10% mortality in control group) (RR 0.79, 95% CI 0.68-0.92, p-value = 0.003), whereas no significant effect was observed for trials of patients with a lower mortality in the control group. 110 The Cochrane Database Systematic Review by Avenell et al (updated 2007) investigating the effects of single-nutrient supplementation, specifically selenium supplementation, including the selenium-containing compound ebselen, concluded: "There is limited evidence to recommend supplementation of critically ill patients with selenium or ebselen".…”
Section: Cccpg Aspen/sccm Espenmentioning
confidence: 95%
See 1 more Smart Citation
“…The latest systematic review, including 21 trials, regarding antioxidant micronutrients in the critically ill confirm the mortality, length of stay and LICU findings by Visser et al, 100 and additionally report a significant reduction in duration of mechanical ventilation (WMD in days = -0.67, 95% CI -1.22 to -0.13, p-value = 0.02) with antioxidant supplementation. 110 Furthermore, antioxidants were associated with a significant reduction in overall mortality in patients with higher risk of death (> 10% mortality in control group) (RR 0.79, 95% CI 0.68-0.92, p-value = 0.003), whereas no significant effect was observed for trials of patients with a lower mortality in the control group. 110 The Cochrane Database Systematic Review by Avenell et al (updated 2007) investigating the effects of single-nutrient supplementation, specifically selenium supplementation, including the selenium-containing compound ebselen, concluded: "There is limited evidence to recommend supplementation of critically ill patients with selenium or ebselen".…”
Section: Cccpg Aspen/sccm Espenmentioning
confidence: 95%
“…110 Furthermore, antioxidants were associated with a significant reduction in overall mortality in patients with higher risk of death (> 10% mortality in control group) (RR 0.79, 95% CI 0.68-0.92, p-value = 0.003), whereas no significant effect was observed for trials of patients with a lower mortality in the control group. 110 The Cochrane Database Systematic Review by Avenell et al (updated 2007) investigating the effects of single-nutrient supplementation, specifically selenium supplementation, including the selenium-containing compound ebselen, concluded: "There is limited evidence to recommend supplementation of critically ill patients with selenium or ebselen". 111 They found no significant differences for overall mortality and infectious complications and no clear evidence of the benefits of such supplementation for ventilator days, LICU, length of stay or quality of life.…”
Section: Cccpg Aspen/sccm Espenmentioning
confidence: 95%
“…5 Laboratory monitoring of nutrient levels is an important part of the assessment and management of all patients receiving nutritional support. 8 This study was aimed at estimating the concentrations of elements which have immune-protective role like copper, zinc, iron and magnesium in children diagnosed with SIRS/sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Manzanares W et al in their meta-analysis concluded that supplementation of trace elements and vitamins with antioxidant activity improves outcome. 8 Despite the effect of SIRS on different nutrients is known, it is not translated into routine clinical practice for management of SIRS/sepsis. 9 Present study was carried out to study profile and magnitude of nutrient (copper, iron, zinc, magnesium) deficiency, effect of duration of illness on nutrient levels, role of their deficiency in hospital acquired infections and outcome in children diagnosed with SIRS/sepsis with associated deficiency of nutrients.…”
Section: Prevalence Of Systemic Inflammatory Responsementioning
confidence: 99%
“…O estresse oxidativo é um estado em que o nível de espécies reativas de oxigênio excede as defesas oxidativas endógenas danificando DNA, RNA, proteínas e membranas celulares. 43 A Vitamina A, C e E estariam implicadas em efeito protetor contra peroxidação de membranas. (44) Na SIRS ocorre redução dos níveis séricos de vitamina por perda capilar, hemodiluição, baixa ingesta e hemodiálise.…”
Section: Antioxidantesunclassified